TURMERIC: NATURE’S PRECIOUS MEDICINE - SHRISHAIL, DUGGI; HARISH K, HANDRAL; RAVICHANDRA, HANDRAL; G.TULSIANAND; SHRUTHI, S.D. (Asian Journal of Pharmaceutical and Clinical Research, 2013)
Ethanobotany is a recent branch of natural science dealing with various aspects such as anthropology, archeology, botany, ecology, economics and medicine, religious, cultural and several other disciplines. Recently, great interest is given to studies of herbal drugs and traditional remedies are indicated worldwide and there has been an upsurge in the scientific investigations in area. Although turmeric (Curcuma longa and Curcuma aromatica Salisb.) has been described in Ayurveda, as treatment inflammatory diseases and is referred by different names in different cultures, active principle called Curcumin or diferuloylmethane, a yellow pigment present in turmeric (curry powder) has been shown to exhibit numerous activities. Extensive research over last fifty years has revealed several important functions of curcumin. The present study was aimed to review the ethanobotanical properties, pharmacognostic, phytochemical and pharmacological properties of turmeric plant. Root part of the plant are widely used by different tribal communities as turmeric have been shown to have wide spectrum of biological actions, which include anti-inflammatory, anti-diabetic, analgesic, antibacterial, anti-fungal, anti-protozoal, anti-ulcer, hypocholesteremic activities. Its anti-cancer effect induced mainly mediated through induction of apoptosis and many more medicinal values. KEYWORDS: Curcuma aromatica Salisb. Ethanobotany, kasthuri turmeric, Pharmacognosy, Phytochemistry, Pharmacology.